Stress hormones and the immunological responses to heat and exercise - Brenner, I.; Shek, P. N.; Zamecnik, J.; Shephard, R. J. (International Journal of Sports Medicine, 1998)
This review focuses on the response of "stress" hormones to heat, exercise (single or repeated bouts), and combinations of these stimuli, with particular reference to their impact upon immune function. Very hot conditions induce a typical stress response, with secretion of catecholamines and cortisol. The catecholamines induce a demargination of leukocytes, and cortisol subsequently causes cells to migrate to lymphoid tissue. Sustained exercise, even in a thermally comfortable environment, induces a larger hormonal response than moderate thermal stress. With moderate exercise, increases in leukocyte numbers are related mainly to plasma norepinephrine concentrations, but with more intense exercise epinephrine concentrations assume a major importance. As exercise continues, plasma cortisol levels also rise, inducing an influx of neutrophils from bone marrow and an efflux of other leukocyte subsets. A combination of exercise and heat stress augments both hormonal and leukocyte responses. But these changes seem to be reversed if temperatures are clamped by exercising in cold water. If a second bout of exercise is performed with an inter-test interval of 30-45 min, neither hormone concentrations nor immune responses show any great cumulative effect under temperate conditions. However, in a hot environment the second exercise bout induces a larger and more persistent neutrophilia. Training influences these various responses mainly by decreasing the stress imposed when exercising at a given absolute work-rate.